Calmodulin Activity Affects the Function of the Odorant Receptor AcerOr2 in Honeybees - Guo, Lina; Xu, Bing; Zhao, Huiting; Guo, Yuan; Jiang, Yusuo (Frontiers in Ecology and Evolution, 2022)
Bees rely on their sensitive olfactory system to perform foraging activities in the surrounding environment. This ability is associated with the existence of olfactory receptors (ORs). In this study, we identified the AcerOr2 (ortholog to the Orco) protein in Apis cerana cerana, which contains a conserved, putative calmodulin (CaM)-binding site indicating that CaM is involved in its function. We used immunofluorescence, western blot, and Ca2+ imaging to monitor changes in the expression and activation of the signaling pathway associated with Ca2+ and Ca2+/calmodulin-dependent protein kinase II (CaMKII) in Sf9 cells heterologously expressing AcerOr2 and a CaM-binding mutant. Use the synthetic Orco agonist VUAA1 to stimulate the cells, or the antagonist W7 to inhibit CaM activity. The AcerOr2 CaM-binding mutant has a point mutation in the putative CaM binding site (K331N). When heterologously expressed in Sf9 cells the mutant should have little CaM activity. When the cells expressing AcerOr2 was treated with W7, the Ca2+ response of AceOr2 was similar to that of the mutant stimulated by VUAA1, and the expression of the CaM, CaMKII and p-CaMKII have the similar affects. Our results suggest that CaM activity affects the function of AceOr2 in vitro and can be used to further study the interaction between the AcerOr2 and calcium/calmodulin signaling pathway in pollen collection behavior of bees.